Dominant stakeholders, activity and accountability discharge in the CSO sector. (17th October 2017) - Cordery, Carolyn J.; Sim, Dalice
Abstract: Civil society organisations (CSOs) comprise a diverse range of associations, including non‐governmental organisations (NGOs), community groups, political parties and social networks. Nevertheless, despite heterogeneity, regulators, funders and donors often treat CSOs as homogeneous when demanding accountability. This paper highlights differences in to whom CSOs across different categories (or types) perceive themselves to be accountable, what for and the different practices they undertake to discharge accountability. It calls for stakeholders to acknowledge diversity in accountability across different CSO types. This survey‐based research finds CSOs weight upwards and downwards stakeholders equally, and undertake voluminous reporting. They would benefit from negotiating multiple‐use mechanisms, especially with dominant stakeholders. In combining stakeholder and accountability theory, the research highlights specific CSO types needing further study.